Ambulatory Care Management in Low Blood Pressure Patient with HFrEF - Panjaitan, Fajar H.; Hasanah, Dian Yaniarti; Yonas, Emir; Soerarso, Rarsari (International Journal of Angiology, 2023)
Heart failure (HF) affects an estimated 38 million people globally, with most published research estimating a prevalence of 1 to 2% of the adult population. Low blood pressure (BP) is reported in 10 to 15% of patients with HF in clinical trials, although this proportion is much more frequent in routine clinical practice. Low BP in outpatients has a better outcome compared to inpatients. Low BP is often a restricting factor in the use and uptitration of guideline-directed medical therapy (GDMT). A 57-year-old male presented himself to the HF clinic with complaints of bloating, shortness of breath, and fatigue. The patient had a history of acute coronary syndrome and cardiac arrest, but the results of coronary angiography showed nonsignificant coronary artery disease. Cardiomegaly was seen on chest X-ray. Electrocardiogram showed pathologic q wave II, III, and AvF with poor r wave progression on V1-V6. The patient was admitted due to acute decompensated HF with hypotension. After the initial decongestion patient was treated with sacubitril/valsartan, bisoprolol, and spironolactone in the outpatient clinic. Patient complaints and BP slowly improved during the outpatient phase. Hypotension remains a challenge in implementing GDMT in HF patients. By following the steps according to algorithm and current guidelines, GDMT can be optimized in these patients.
Keywords: heart failure with reduced ejection fraction; low blood pressure; ambulatory patient